A Comparison of Patient Satisfaction with Emergency Department Opt-In and Opt-Out Rapid HIV Screening. (16th February 2012) - White, Douglas A. E.; Scribner, Alicia N.; Martin, Maria E.; Tsai, Stacy
Abstract : Study objective . To compare patient satisfaction with emergency department (ED) opt-in and opt-out HIV screening. Methods . We conducted a survey in an urban ED that provided rapid HIV screening using opt-in (February 1, 2007–July 31, 2007) and opt-out (August 1, 2007–January 31, 2008) approaches. We surveyed a convenience sample of patients that completed screening in each phase. The primary outcome was patient satisfaction with HIV screening. Results . There were 207 and 188 completed surveys during the opt-in and opt-out phases, respectively. The majority of patients were satisfied with both opt-in screening (95%, 95% confidence interval [CI] = 92–98) and opt-out screening (94%, 95% CI = 89–97). Satisfaction ratings were similar between opt-in and opt-out phases even after adjusting for age, gender, race/ethnicity, and test result (adjusted odds ratio 1.3, 95% CI = 0.5–3.1). Conclusions . Emergency department patient satisfaction with opt-in and opt-out HIV screening is similarly high.